My Hero Academia. Vol. 26, The high, deep blue sky - Horikoshi, Kōhei, 1986-; Cook, Caleb D. (San Francisco, CA : VIZ Media, LLC, 2021)
While preparing for a big villian attack, Eraser Head and Present Mic pay a visit to Tartarus prison, while Midoriya, Bakugo, and Todoroki begin training under Endeavor in order to become fighters who can stand on their own.
Pages numbered from right to left.
Keywords: Graphic novels